PRACTICAL APPLICATIONS OF DESCRIPTIVE GEOMETRY IN CADASTRE AND GEOGRAPHIC INFORMATION SYSTEMS: ENHANCING SPATIAL DATA ACCURACY AND ANALYSIS - Yuldashev Salmonxon Iqboljon ugli (Modern American Journals, 2025)
Descriptive Geometry plays a critical role in cadastre management and Geographic Information Systems (GIS), providing the mathematical and visual foundation for accurate spatial data representation, analysis, and decision-making. With the growing demand for precise land surveying, property delineation, and geospatial analysis, integrating Descriptive Geometry into cadastre and GIS workflows enhances data accuracy, reduces errors, and improves the efficiency of spatial operations. This study investigates practical applications of Descriptive Geometry in cadastre and GIS contexts, focusing on methods, digital tools, and workflow integration. Following the IMRaD structure, the research combines literature review, case studies of cadastral mapping projects, and experimental application of geometric methods in GIS software. Results demonstrate that applying Descriptive Geometry principles improves spatial data integrity, facilitates 3D modeling of land parcels, and enhances analytical capabilities for planning, resource management, and legal documentation. The discussion addresses technological integration, methodological challenges, and pedagogical implications for training surveyors and GIS professionals. The conclusion emphasizes that modern applications of Descriptive Geometry are essential for optimizing cadastral and GIS operations, ensuring precision, and supporting informed decision-making in spatial management.
Keywords: Descriptive Geometry, Cadastre, GIS, Spatial Data, 3D Modeling, Surveying, Geoinformatics, Mapping Accuracy.